The current Indian epidemic of dermatophytosis: A study on causative agents and sensitivity patterns - Sudip Das; Abhishek De; Rajdeep Saha; Nidhi Sharma; Monika Khemka; Sonal Singh; Abu Hena Hesanoor Reja; Purushottam Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: In the recent years, the frequency, severity, clinical characteristics, treatment response, and relapse rate of dermatophytosis have dramatically changed in India. Given the surge in dermatophytosis, we had undertaken a study to isolate and identify the common species causing dermatophyte infection and to know the in vitro efficacy of the common antifungals against them. Materials and Methods: total of 103 new cases that were not on any treatment for the past 3 months were included. Skin scrapings were collected for direct microscopic examination and for fungal culture in Sabouraud 4% dextrose agar (SDA) with chloramphenicol and cycloheximide slant tubes, and dermatophyte test media. Fungi were identified on the basis of their macroscopic and microscopic features with the help of lactophenol cotton blue staining and urease test. Also, the drug sensitivity of the dermatophytes was tested with the common antifungals. Results: Of the 55 cases (53.4%) that were positive for dermatophytes in the culture, 29 showed possible contamination. Trichophyton was the predominant organism (49 cases) with T. verrucosum being the commonest species (26 cases), followed by T. rubrum (15 patients), and T. mentagrophytes(8 cases). All species of Trichophyton were found to be most sensitive to itraconazole amongst systemic antifungals and luliconazole amongst topical antifungals. Conclusion: This study concluded that the causative agent for the dermatophytosis was changing in India and in our subset, T. verrucosum caused the maximum number of infections. Itraconazole and luliconazole had the highest sensitivity amongst systemic and topical antifungals, respectively. It also showed that terbinafine had comparatively less sensitivity to most organisms.